(untitled) (Biological Sciences - PJSIR, 1998)
Forty nine Catla catla samples of variable sizes caught from the River Chenab, Pakistan were studied for inorganic elemental concentrations in relation to body size. It was observed that the total quantity of elements i.e. sodium, potas- sium, calcium, magnesium, manganese, iron, nickel, copper, zinc and lead was found to increase isometrically with body weight. Whereas only sodium, potassium, magnesium, zinc and lead showed positive allometry and the remaining ele- ments showed isometry with increasing length. Cobalt, chromium and cadmium were not quantifiable.